The effect of calibration errors on the accuracy of the eye movement recordings - Jörg Hoormann; Stephanie Jainta; Wolfgang Jaschinski (Bern Open Publishing, 2008)
For calibrating eye movement recordings, a regression between spatially defined calibration points and corresponding measured raw data is performed. Based on this regression, a confidence interval (CI) of the actually measured eye position can be calculated in order to quantify the measurement error introduced by inaccurate calibration coefficients. For calculating this CI, a standard deviation (SD) - depending on the calibration quality and the design of the calibration procedure - is needed. Examples of binocular recordings with separate monocular calibrations illustrate that the SD is almost independent of the number and spatial separation between the calibration points - even though the later was expected from theoretical simulation. Our simulations and recordings demonstrate that the SD depends critically on residuals at certain calibration points, thus robust regressions are suggested.